The Implementation of Game-Based Learning in Sociology Class X-2 at SMA Negeri 8 Surakarta - Inayah, Nur'aini; Kartika Hanindra Putri, Eufrasia; Dwi Permata Indah, Putri; Syaifullah, Khalid (Ittishal Educational Research Journal, 2024)
The evolving demands of the times necessitate that educators develop innovative and engaging learning experiences for their students. Additionally, teachers as facilitators, must also be able to understand the needs of their students. When students experience a decline in motivation during lessons, it is necessary for teachers to take action. This situation occurred in class X-2 at SMA Negeri 8 Surakarta. The categorization results showed that 66% of the students had low motivation in learning. Therefore, it is essential for the teacher to take action to address the low learning motivation among the students. This study aims to examine the effectiveness of implementing game-based learning to increase students' motivation. The research was conducted through classroom action research over two cycles. Both cycles applied game-based learning to the material on various social phenomena and social research. The number of students participating in the study was 36. Data collection was carried out through observation and reflection after the lessons were conducted. The results showed an increase in students' learning motivation after the intervention. Thus, it can be concluded that the implementation of game-based learning can be an innovative and engaging alternative for students.